APPLICATION OF THE ACCRUAL-BASED AGENCY ACCOUNTING SYSTEM (SAIBA) AS THE IMPLEMENTATION OF PP NO. 71 OF 2010 IN THE PREPARATION OF FINANCIAL STATEMENTS AT THE OFFICE OF THE MINISTRY OF REGION OF POHUWATO REGENCY - monitasary; Ibrahim, Meimoon; Tahir, Arifin (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The objectives of this study are: 1) The application of an accrual-based agency accounting system as the implementation of PP 71 of 2010 in the preparation of financial reports at the Office of the Ministry of Religion of Pohuwato Regency; 2) What are the factors that influence the application of the accrual-based agency accounting system (SAIBA) in the preparation of financial reports at the Office of the Ministry of Religion of Pohuwato Regency This study uses research conducted using a qualitative approach while the type of research used in this thesis research is qualitative descriptive research. The results of this study indicate that: 1) The application of the accrual-based agency accounting system has been carried out well. Judging from the relevance indicator. the implementation of accrual-based Government Accounting Standards (SAP) at the Ministry of Religion of Pohuwato Regency has been based on Government Regulation Number 71 of 2010, and is compiled in full which consists of reports 2) Application of accrual-based agency accounting systems as the implementation of PP 71 of 2010 in the preparation of financial statements in The Office of the Ministry of Religion of Pohuwato Regency includes human resources, socialization.